(untitled) (Euro-Asia Conferences, 2021)
The interest shown by scientists around the world to human heredity is not accidental. Currently, about 2000 hereditary diseases and genetically determined syndromes are known. Their number is constantly growing, dozens of new forms of hereditary pathology are described every year. At the present stage of development of medicine, recognition of various hereditary diseases and genetically determined syndromes is of exceptional importance.The lack of a generally accepted classification of hereditary diseases, their large polymorphism and the large number of phenocopies create difficulties in the diagnosis and differential diagnosis of heredial forms of pathology